What Works Best When Combining Television Sets, PCs, Tablets, or Mobile Phones? How Synergies Across Devices Result From Cross-Device Effects and Cross-Format Synergies - Varan, D.; Murphy, Jamie; Hofacker, C.; Robinson, J.; Potter, R.; Bellman, S. (World Advertising Research Center, 2013)
Advertising research often confounds device effects (e.g., television sets, radios, and personal computers) with communication format effects (e.g., respectively, video, audio, and Web sites). Across four experiments, this study documents empirical patterns of cross-device effects among television sets, PCs, iPods, and mobile phones. In three experiments, the format was identical across devices, and the device made no difference to advertising effectiveness. The fourth experiment—with different formats and devices—showed sequential synergy effects. Synergy can strengthen or weaken advertising campaigns that combine multiple communication devices. The combined results of four experiments suggest possible cross-format synergies but not cross-device synergies.